Image compression module based neural network autoencoders - Lesyk, V.O.; Doroshenko, А.Yu. (Інститут програмних систем НАН України, 2023)
A new approach is proposed to data compression in the form of a neural network module based on the structure of autoencoders, which has the most optimal learning time, compression level and obtains sufficiently clear image reconstruction. The main mechanisms for building the structure of encoder and decoder neural networks, which are used as a module, have been developed. The main data for the reconstruction were selected from the open data set Fashion-MNIST, which allows simplified testing of neural network structures, the process of their training and obtaining results. Approaches to image reproduction using neural network layers of convolution and inverse convolution are analyzed. An analysis of the impact on the quality of the resulting image reconstruction of the structure of the output module, which is used to compress the input image, was carried out. Atypical behavior was found during the increase of layers in the structure of the autoencoder, which did not lead to an increase in the quality of image reproduction. The basic necessity of changing the structural parts of the autoencoder and its application in combination with other technologies to obtain a better reproduction result and the elimination of distortions is highlighted.Prombles in programming 2023; 1: 48-57